Prognostic Relevance of Weight and Weight Loss during Multimodal Therapy for Oesophagogastric Tumours - Alessandro Lorusso; Dmitry Bichev; Anica Högner; Prisca Bartels; Alexej Ballhausen; Christoph Treese; Matthias Biebl; Peter Thuss-Patience (Current Oncology, 2022)
The prognostic meaning of weight loss (WL) during standard treatment for operable oesophagogastric cancer is still unclear. The aim of this study is to analyse the prognostic effect of WL during perioperative chemotherapy (PC) for gastric cancer (GC) and oesophageal adenocarcinomas (OAC). We retrospectively analysed data from 128 patients (pts) with GC and OAC who underwent surgery in the context of multimodal treatment with PC. We collected data on WL during different steps of therapy together with other histopathologic and demographic information. We analysed the effects on overall survival (OS) and disease-free survival (DFS). Results: Pts with WL ≥ 5% during neoadjuvant chemotherapy exhibited significantly worse OS compared with pts with WL < 5% (median OS: 23.6 months [95% CI: 4.4–42.9] vs. 63.5 months [95% CI: 50.7–76.2], p = 0.007) and DFS (median DFS: 12.5 months [95% CI: 2.9–22.1] vs. 63.5 months [95% CI: 31.6–95.4], p = 0.016). Pts with WL ≥ 14% during the whole treatment exhibited significantly worse OS compared with pts with WL < 14% (median OS: 43.7 months [95% CI: 13.2–74.2] vs. not reached, p = 0.028) and DFS (median DFS: 34.3 months [95% CI: 14.0–54.5] vs. not reached, p = 0.038). Conclusion: WL patterns during neoadjuvant chemotherapy and during the whole treatment correlate with a significantly worse prognosis in operated pts with curative GC or OAC in the context of a multimodal treatment with PC. A validation of this prognostic effect in prospective studies is warranted.